The religious/spiritual beliefs and needs of cancer survivors who underwent cancer-directed surgery. Issue 2 (April 2021) - Palmer Kelly, Elizabeth; Paredes, Anghela Z.; DiFilippo, Stephanie; Hyer, Madison; Tsilimigras, Diamantis I.; Rice, Daniel; Bae, Junu; Pawlik, Timothy M.
Abstract: Objective: We sought to characterize patients' preferences for the role of religious and spiritual (R&S) beliefs and practices during cancer treatment and describe the R&S resources desired by patients during the perioperative period. Method: A cross-sectional survey was administered to individuals who underwent cancer-directed surgery. Data on demographics and R&S beliefs/preferences were collected and analyzed. Results: Among 236 participants, average age was 58.8 (SD = 12.10) years; the majority were female (76.2%), white (94.1%), had a significant other or spouse (60.2%), and were breast cancer survivors (43.6%). Overall, more than one-half (55.9%) of individuals identified themselves as being religious, while others identified as only spiritual (27.9%) or neither (16.2%). Patients who identified as religious wanted R&S integrated into their care more often than patients who were only spiritual or neither ( p < 0.001). Nearly half of participants (49.6%) wanted R&S resources when admitted to the hospital including the opportunity to speak with an R&S leader (e.g., rabbi; 72.1%), R&S texts (64.0%), and journaling materials (54.1%). Irrespective of R&S identification, 68.0% of patients did not want their physician to engage with them about R&S topics. Significance of results: Access to R&S resources is important during cancer treatment, and incorporating R&S into cancer care may be especially important to patients that identify as religious. R&S needs should be addressed as part of the cancer care plan.